Oestrogen exposure and breast cancer risk. - Travis, R; Key, T (2003)
Epidemiological and experimental evidence implicates oestrogens in the aetiology of breast cancer. Most established risk factors for breast cancer in humans probably act through hormone-related pathways, and increased concentrations of circulating oestrogens have been found to be strongly associated with increased risk for breast cancer in postmenopausal women. This article explores the evidence for the hypothesis that oestrogen exposure is a major determinant of risk for breast cancer. We review recent data on oestrogens and breast cancer risk, consider oestrogen-related risk factors and examine possible mechanisms that might account for the effects of oestrogen. Finally, we discuss how these advances might influence strategies for reducing the incidence of breast cancer.